Effects of 2.0% Equiverm in high doses on the clinical state of the horses’ organism - M. B. Musaev; N. B. Emelyanova; E. E. Belova (Российский паразитологический журнал, 2022)
The purpose of the research is to study the effect of the new antiparasitic 2.0% Equiverm in high doses on the clinical state of horses.Materials and methods. The experiment was conducted on 15 two-year-old crossbred horses weighing up to 300 kg spontaneously infected with Strongylata. To determine the effect of the antiparasitic paste on the horses, three groups of five horses each were formed. The first group of the horses was administered 2.0% Equiverm at a therapeutic dose; the second, at a three-fold increased dose, and the third, at a five-fold increased dose (0.2; 0.6 and 1.0 mg/kg for the active substance (AS), and 1.0; 3.0 and 5.0 mL per 100 kg of body weight for the drug). The horses’ clinical state was studied using standard methods. Blood samples for the study were taken from the jugular vein before the drug on the first, third and seventh days. The results obtained were statistically processed using the computer tool Microsoft Excel 2007.Results and discussion. It was found that the antiparasitic paste 2.0% Equiverm had no negative effect on clinical, hematological or biochemical parameters after a single oral administration at a therapeutic, three- and five-fold increased dose (0.2; 0.6 and 1.0 mg/kg for the AS, and 1.0; 3.0 and 5.0 mL per 100 kg of the body weight for the drug).